2020
DOI: 10.3389/fphar.2019.01672
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Physiologically Based Pharmacokinetic Modeling Approach to Guide Optimal Dosing Regimens for Imatinib and Potential Drug Interactions in Paediatrics

Abstract: Long-term use of imatinib is effective and well-tolerated in children with chronic myeloid leukaemia (CML) yet defining an optimal dosing regimen for imatinib in younger patients is a challenge. The potential interactions between imatinib and coadministered drugs in this "special" population also remains largely unexplored. This study implements a physiologically based pharmacokinetic (PBPK) modeling approach to investigate optimal dosing regimens and potential drug interactions with imatinib in the paediatric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(60 citation statements)
references
References 111 publications
0
60
0
Order By: Relevance
“…43 In the case of imatinib PBPK model (children > 2 years old), no significant differences were observed. 44 However, no studies reported systematic comparisons of these hepatic CYP3A4 ontogeny functions for the evaluation of DDI risk in children.…”
Section: Discussionmentioning
confidence: 99%
“…43 In the case of imatinib PBPK model (children > 2 years old), no significant differences were observed. 44 However, no studies reported systematic comparisons of these hepatic CYP3A4 ontogeny functions for the evaluation of DDI risk in children.…”
Section: Discussionmentioning
confidence: 99%
“…As carbamazepine plays a crucial role in the treatment of epilepsy (recommended as first line treatment option by Cochrane [ 11 ] and included in the World Health Organization (WHO) Model List of Essential Medicines [ 12 ]), surveillance and examination of its DDI potential is important to ensure a safe drug therapy. The FDA recommends the use of carbamazepine as CYP3A4 and CYP2B6 inducer in clinical drug–drug interaction studies and it was applied in recent clinical trials, for example, with etonorgestrel, basimglurant or bitopertin [ 13 ]. In this case, the physiologically based pharmacokinetic (PBPK) modeling technique can come in as a helpful tool.…”
Section: Introductionmentioning
confidence: 99%
“…More than 60% of PBPK models submitted to the FDA investigate DDIs. Several published studies investigate the DDI potential of carbamazepine using a PBPK modeling approach [ 13 , 16 , 17 , 18 , 19 ]. While carbamazepine is typically used as an inducer to investigate the interaction with a substrate, our study aims to provide a comprehensive overview on the pharmacokinetics of carbamazepine and its DDIs, investigating carbamazepine not only as inducer but also as victim drug.…”
Section: Introductionmentioning
confidence: 99%
“…Input parameters for the PBPK model of imatinib and bosutinib 59 are summarised in Table S1. Development and verification of the PBPK model of imatinib in adults from European ancestry at both single‐dose administration and steady‐state have been detailed elsewhere 60 . The PBPK model was also verified against clinical pharmacokinetic data in people from Chinese ancestry (unpublished).…”
Section: Methodsmentioning
confidence: 99%